Severe Facial Herpes Vegetans and Viremia in NFKB2-Deficient Common Variable Immunodeficiency - Parsons, Karyn; Cipriano, Sarah D.; Rosen, Lindsey B.; Browne, Sarah K.; Walter, Jolan E.; Stone, Bryan L.; Keeshin, Susana; Chen, Karin (Frontiers in Pediatrics, 2019)
With the accessibility of next-generation sequencing modalities, an increasing number of primary immunodeficiency disorders (PIDDs) such as common variable immunodeficiency (CVID) have gained improved understanding of molecular pathogenesis and disease phenotype with the identification of a genetic etiology. We report a patient with early-onset CVID due to an autosomal dominant loss-of-function mutation in NFKB2 who developed a severe herpes vegetans cutaneous infection as well as concurrent herpes simplex virus viremia. The case highlights features of CVID, unique aspects of NF-κB2 deficiency including susceptibility to herpesvirus infections, the detection of neutralizing anticytokine antibodies, and the complexity of medical management of patients with a PIDD that can be aided by a known genetic diagnosis.